The Effect of Energy Density on Microstructural, Mechanical, and Corrosion Characteristics of Ti-6Al-4V Alloy Fabricated via Selective Laser Melting and Electron Beam Melting Techniques - Yilmazer, H.; Sadikoglu, Y. A.; Kucuk, S.; Gokcekaya, O.; Turu, I. C.; Nakano, T.; Dikici, B. (SPRINGER, 2025)
In this study, the effect of production parameters on Ti-6Al-4V alloys fabricated using selective laser melting (SLM) and electron beam melting (EBM) techniques was investigated. Through the variation of energy volume (12.5, 25, 37.5 J mm-3), these two additive manufacturing methods were compared in terms of microstructure, mechanical, and corrosion properties. Density was calculated using Archimedes' technique, while microstructure was characterized through optical microscopy (OM) and scanning electron microscopy (SEM). Mechanical properties were determined via micro-Vickers hardness and tensile tests. Electron backscatter diffraction (EBSD) and x-ray diffraction (XRD) analyses were performed on EBM and SLM samples for a comprehensive understanding. Corrosion susceptibilities of the alloys were evaluated using potentiodynamic scanning (PDS) tests in a 3.5% NaCl solution at room temperature. Microstructural analysis revealed that SLM-produced parts predominantly consisted of the alpha ' (martensite) phase, whereas EBM-produced parts primarily comprised the alpha phase with a small amount of the beta phase. The strength values of all SLM samples exceeded 930 MPa, surpassing those of wrought Ti-6Al-4V ELI. However, only EBM samples fabricated with a 37.3 J mm-3 energy volume approached this standard. Corrosion susceptibility generally increased with higher energy volume in both EBM and SLM samples, with porosity volume and grain size variations influencing corrosion behavior.
Keywords: Corrosion; EBM; Energy density; Phase transformation; SLM; Ti-6Al-4V; BEHAVIOR; COMPONENTS; Materials Science